Analisis Tuntutan Jaksa Penuntut Umum Terhadap Pelaku Tindak Pidana Judi Online (Studi Kasus Terdakwa Aditya Bin Noviar : Kejaksaan Negeri Agam) - Chicha Idia Roza; Sukmareni (Cattleya Darmaya Fortuna, 2026)
The development of information technology has led to the emergence of new forms of crime, one of which is online gambling. Although it is strictly regulated in Articles 303 and 303 bis of the Criminal Code (KUHP), as well as Article 27 paragraph (2) in conjunction with Article 45 paragraph (2) of Law No. 1 of 2024 on Information and Electronic Transactions (ITE Law), law enforcement against online gambling perpetrators still faces various challenges, including in the prosecution process. This study aims to analyze the legal considerations of the Public Prosecutor (JPU) in formulating criminal charges against the defendant Aditya bin Noviar in case Number 32/Pid.B/2025/PN Lbb. This study uses a normative juridical method with a legislative approach, a case approach, and a conceptual approach. Data was obtained from primary, secondary, and tertiary legal materials. The results of the study show that the conventional approach through the Criminal Code still dominates the prosecution strategy, even though the crimes being handled have transformed into digital forms. This study concludes that the prosecution strategy against online gambling perpetrators needs to be more adaptive, targeted, and reflect strong legal protection for the community. The findings show that the criminal charge of 1 (one) year imprisonment was based on consideration of evidence, trial facts, and aggravating and mitigating circumstances of the defendant, thus reflecting the application of the principles of legality and proportionality. The charges are formally in accordance with Article 303 paragraph (1) 2 of the Criminal Code, but are considered relatively light when linked to the characteristics of online gambling as a crime based on information technology. The use of Article 303 of the Criminal Code was chosen because the elements of the offense in the ITE Law were not proven, so the principle of lex specialis could not be applied.